Les genres récrits n° 2 - Daniel Elmiger (Glad!)
For non-sexist (or inclusive) writing, abbreviated double forms (such as “étudiant·e·s”) are one of the possible resources to be exploited. In general, the signs used for abbreviations (dots, dashes or brackets) are relatively few in number. With the help of a text that is saturated with other formal processes, many alternative possibilities—sometimes useful, sometimes playful ones—are presented in this column.